Finding Her Voice Through Scriptotherapy: Marina Nemat’s Journey of Reclaiming Subjectivity after Trauma - Hooshmandasl, Elaheh; Sabouri, Hossein; Ameri, Firouzeh (International Journal of Language and Literary Studies, 2024)
Scriptotherapy, a form of writing therapy proposed by Suzette Henke, is gaining recognition in literary research but remains underrepresented in studies of Iranian diasporic literature, which often focus on identity crisis and Orientalist discourse. This paper explores the application of scriptotherapy in Marina Nemat’s memoirs, Prisoner of Tehran (2007) and After Tehran (2010), revealing the significant role of therapeutic writing in reclaiming subjectivity fragmented by trauma. As a teenager advocating for legislative reformation in 1980s Iran, Nemat faced legal consequences and two years of imprisonment, leaving enduring psychological wounds. Years after her release, disturbing memories and enduring silence compelled Nemat to utilize writing for catharsis. Through writing, Nemat confronts and transcends her haunting past, embarking on a transformative journey of healing and reclaiming her voice within an intersubjective realm. This paper emphasizes the importance of an audience as witnesses to trauma and discusses obstacles faced by women who bear witness, particularly when their testimonies involve institutional abuse and patriarchal constraints. This analysis demonstrates scriptotherapy’s transformative potential, empowering trauma survivors like Nemat to heal from the wounds of their traumatic pasts, ultimately enabling them to regain a profound sense of subjectivity, despite doubts about the authenticity of their narratives.